PENGARUH EDUKASI FARMASIS TERHADAP KEPATUHAN DAN KONTROL GLIKEMIK PASIEN DM TIPE 2 PENGGUNA INSULIN DI POLIKLINIK PENYAKIT DALAM RSUD BAYU ASIH KABUPATEN PURWAKARTA TAHUN 2013 - Suharti, Suharti; Tamat, Swasono R.; Keban, Sesilia A. (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background: Diabetes mellitus (DM) is a heterogeneous group of disorders characterized by an increase in blood glucose levels or hiperglikemia that occurs due to abnormal insulin secretion, insulin action or both. Drug therapy is safe and effective would happen if patients were given enough information about medicine and its usage. Objectives This study aims to determine the role of pharmacists in educating patients about diabetes melitus and its relation with factors that influencing glycemic control in type 2 diabetes patients, in Internal Disease Clinic at Bayu Asih Purwakarta Hospital. Methods: The study is an experimental study conducted using Nonrandomized Concurrent Control Trial prospectively. Patients were devided into three groups with 20 patients in each group, who were given education by pharmacist with different frequency, first group given education twice, second group given education 3 times, and third group given education 4 times. Patient’s knowledge on medication were measured by the Medication Knowledge Assessment (MKA), whereas adherence to medication were measured using Modified Morisky Scale (MMS). Data collected were analyzed descriptively and also quantitatively by independent t test and paired t test.   Result. The results showed that the patients in the group 2 times education, group 3 times education and group 4 times education, all of them experienced an increase in the level of knowledge and compliance. In addition, patients in the three groups also experienced a decrease in their fasting blood sugar (GDP) and two-hour blood sugar levels (GD2JPP), however, the difference in the frequency of education did not affect the level of knowledge, compliance and also blood sugar levels of patients. The study concluded that pharmacist education can improve knowledge and medication adherence. There was no correlation between patient adherence and glycemic control, but there was a positive correlation between frequency of education and blood glucose levels 2 hours post prandial. There are no correlation between adherence and glycemic control, but is a positive correlation between frequency of education and 2 hour post prandial blood glucose level. Conclusion. It can be cocluded also that frequency of education can influence on adherence and glycemic control.